Making medical decisions for an incompetent older adult when both a proxy and an advance directive are available: which is more likely to reflect the older adult's preferences?. Issue 7 (9th March 2018) - Bravo, Gina; Sene, Modou; Arcand, Marcel
Abstract : Objectives: To investigate which of two sources of information about an older adult's wishes—choices made in an advance directive or proxy's opinion—provides better insight into the older adult's preferences measured in hypothetical clinical situations involving decisional incapacity. Methods: Secondary analyses of data collected from 157 community-dwelling, decisionally competent adults aged 70 years and over who attended a group information session on advance directives with their proxy. Older adults were invited to complete a directive introduced during the session, designed to express healthcare preferences. An average of 3 months later, older adults were asked during an interview whether they would want to receive each of four medical interventions and what their goals of care would be should they develop one of three sudden health events, assuming that they had severe dementia. Proxies were asked to guess the older adult's answers in each of the seven scenarios. Results: Eighty per cent of the older adults completed the directive. Choices they made in the directive were more in line with the preferences they stated during the interview than were their proxies' guesses at their answers. However, concordance was relatively low, with percentages of agreement ranging from 43% to 83% across scenarios. Conclusions: Findings suggest that a directive might provide better insight into a person's wishes than the person's proxy, although neither source is perfect. A multifaceted decision-making model that includes both sources of information might better serve the interests of older adults who have lost the capacity to make decisions on their own. Trial registration number: ISRCTN89993391 ; Post-results.